1995
DOI: 10.1164/ajrccm.152.1.7599830
|View full text |Cite
|
Sign up to set email alerts
|

Airway obstruction during exercise in asthma.

Abstract: Airway obstruction (AO) in exercise-induced asthma (EIA) is considered a postexercise phenomenon. However, many with EIA complain of respiratory distress during exercise. We evaluated AO in six asthmatic subjects during a short (SX = 6 min) and a long (LX = 20 min) exercise session. We measured peak expiratory flow (PEF) rate, forced expiratory volume in one second (FEV1), and forced expiratory flow at 50% of vital capacity (Vmax50) and calculated expiratory and inspiratory pulmonary resistance (RLe and RLi). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 22 publications
6
32
0
Order By: Relevance
“…Indirect evidence suggests that hyperinflation is not the sole mechanism of dyspnoea: some patients with chronic asthma have a minimal increase in lung volume but are quite symptomatic. Previous studies have found that there is no airway obstruction or dynamic hyperinflation (DH) during short-term intense exercise sessions in mild-to-moderate asthma [13,14]. SUMAN et al [13] reported that there was little or no airway obstruction during short-term exercise, with obstruction and mild DH only evident during the late stage of long-term exercise sessions in patients with exercise-induced asthma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indirect evidence suggests that hyperinflation is not the sole mechanism of dyspnoea: some patients with chronic asthma have a minimal increase in lung volume but are quite symptomatic. Previous studies have found that there is no airway obstruction or dynamic hyperinflation (DH) during short-term intense exercise sessions in mild-to-moderate asthma [13,14]. SUMAN et al [13] reported that there was little or no airway obstruction during short-term exercise, with obstruction and mild DH only evident during the late stage of long-term exercise sessions in patients with exercise-induced asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that there is no airway obstruction or dynamic hyperinflation (DH) during short-term intense exercise sessions in mild-to-moderate asthma [13,14]. SUMAN et al [13] reported that there was little or no airway obstruction during short-term exercise, with obstruction and mild DH only evident during the late stage of long-term exercise sessions in patients with exercise-induced asthma. Moreover, no relationship was found between dyspnoea and DH during short-or long-term exercise sessions [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations